Questioning Food Security in Green Constitution Conception: Realizing Sustainable Development Goals (SDGs) in Indonesia - Subekti, Rahayu; Husna, Tsabbita Ahmilul; Salsabila, Putri Balqis (Faculty of Law, Universitas Padjadjaran, 2024)
Research on the constitution, food security, and sustainable development have become widely explored. However, issues related to the legal framework in the context of a green constitution remain unresolved. This is particularly evident in Indonesia’s efforts to address the food crisis, which has led to substantial deforestation. Therefore, this research aims to analyze the implementation of food security efforts in line with a green constitution in Indonesia. Despite the potential for adopting sustainability for future generations, there is hesitance in implementing articles related to a green constitution in food security activities. This legal issue is examined as normative research using conceptual and comparative methods and deductive logic. The results show that, firstly, food security is a pillar in achieving Sustainable Development Goals (SDGs), necessitating the correction of erroneous paradigms to optimize the strategic project. The urgency of the implementation in line with sustainable development is based on five fundamental points: conservation of natural resources, environmental protection, social welfare, sustainable economic growth, and fulfilling future needs. Secondly, legislation firmly establishes the significance of sustainable development principles to prioritize environmental consciousness. In addition, there is a need for reformulation in Article 33 paragraph (3) of the 1945 Constitution of Indonesia by adding wording or explanations. This would regulate the limitations of environmental exploitation for community prosperity and establish regulations for development without shifting agricultural land and food production.